Associations of thyroid hormones and resting heart rate in patients referred to coronary angiography - Steinberger, Eva; Pilz, Stefan; Trummer, Christian; Theiler-Schwetz, Verena; Reichhartinger, Markus; Benninger, Thomas; Pandis, Marlene; Malle, Oliver; Keppel, Martin Helmut; Verheyen, Nicolas; Grübler, Martin R.; Völkl, Jakob Georg Jonathan; et al. (Hormone and metabolic research, 2020)
Resting heart rate (RHR) is associated with increased risk of cardiovascular morbidity and mortality. Thyroid hormones exert several effects on the cardiovascular system, but the relation between thyroid function and RHR remains to be further established. We evaluated whether measures of thyroid hormone status are associated with RHR in patients referred to coronary angiography. Thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxin (FT4), and RHR were determined in 2795 participants of the Ludwigshafen Risk and Cardiovascular Health (LURIC) Study. Median (25th to 75th percentile) serum concentrations were 1.25 (0.76-1.92) mU/l for TSH, 4.8 (4.2-5.3) pmol/l for FT3 and 17.1 (15.4-19.0) pmol/l for FT4, and mean (±standard deviation) RHR was 68.8 (±11.7) beats/min. Comparing the highest versus the lowest quartile, RHR (beats/min) was significantly higher in the fourth FT4 quartile [3.48, 95% confidence interval (CI): 2.23-4.73; p <0.001] and in the fourth FT3 quartile (2.30, 95% CI: 1.06-3.55; p <0.001), but there was no significant difference for TSH quartiles. In multiple linear regression analyses adjusting for various potential confounders, FT3 and FT4 were significant predictors of RHR (p <0.001 for both). In subgroups restricted to TSH, FT3, and FT4 values within the reference range, both FT3 and FT4 remained significant predictors of RHR (p <0.001 for all). In conclusion, in patients referred to coronary angiography, FT3 and FT4 but not TSH were positively associated with RHR. The relationship between free thyroid hormones and RHR warrants further investigations regarding its diagnostic and therapeutic implications.